Cells perpetuating the inflammatory response in scleritis. Issue 5 (May 1994) - Bernauer, W; Watson, P G; Daicker, B; Lightman, S
Abstract : Scleritis can be a destructive disease frequently associated with autoimmune disorders. It is believed that primary vasculitis plays an important role in its pathogenesis, but little is known about the cellular effector mechanisms. The purpose of this study was to analyse the inflammatory cellular infiltrate in scleritis. Six episcleral biopsies and two enucleated eyes were studied. The episcleral biopsies were taken from patients with nodular scleritis. In one patient enucleation was done after perforation in anterior necrotising scleritis and, in the other after misdiagnosis of posterior scleritis as intraocular tumour. Morphological criteria and immunohistochemical methods were used to characterise the inflammatory cellular infiltrate. The inflammatory cells infiltrating the episcleral tissue were mainly T lymphocytes and macrophages. There was a predominance of CD4 positive cells, but only few lymphocytes were activated (expressed IL-2 receptor). The cells infiltrating the scleral fibres in the enucleated eyes consisted in both cases predominantly of T cells. Clusters of B cells were found in perivascular areas. In circumscribed areas neutrophils, macrophages, and plasma cells were part of the scleral infiltrate. Signs of a granulomatous process with activated macrophages (epithelioid and giant cells) were present in necrotising scleritis. Expression of major histocompatibility class II molecules (MHC II) was found on lymphocytes and rarely on macrophages. Signs of primary vasculitis were not found in any of the specimens. The cellular infiltrate in scleritis shows, at least at certain stages, features compatible with a T cell mediated (autoimmune) disorder, which may have major therapeutic implications.